The dark side of leadership : identifying and overcoming unethical practice in organizations - Normore, Anthony H.; Brooks, Jeffrey S., 1970- (Bingley : Emerald Group Publishing Limited, 2016)
This book explores the dark side of leadershipthose areas of unethical, unlawful and unconscionable practice in which some organizational leaders engage. Each chapter addresses a unique aspect of such practice, and takes on difficult (and often ignored) topics such as lying, deliberate miscommunication, racism, corruption, sexism, ageism, greed, abuse of power, and recruiting and promoting unqualified personnel to leadership positions. The authors identify organizational issues and problems while also offering solutions to improve leadership practices that prevent interpersonal, organizational, and institutional toxicity. The general content is framed by, but not limited to, theoretical frameworks, such as ethics, values, chaos and complexity theory, power, free will, trust, critical race theory, systems theory, cultural (in)competency, and social justice. Importantly, the book includes scholars from around the world (e.g., Canada, Australia, Israel, USA) and learners of leadership from across sectors such as higher education, K-12 education, public safety, communication, business, and other relational-oriented fields of inquiry and practice.
Prelims --'Irresponsible leadership' and unethical practices in schools: a conceptual framework of the'dark side' of educational leadership -- Anatomy of an organizational train wreck: a failed leadership paradigm -- A consideration of ethical leadership in ontario university governance -- Rethinking leadership in k-12: ensuring that those in positions of leadership are also positioned to lead -- Unethical decision-making of school principals and vice-principals in the arab education system in israel: the interplay between culture and ethnicity --'strong people dont need strong leaders' -- Coming in from out of the dark -- The destructive effects of distrust: leaders as brokers of trust in organizations -- Global core leadership competencies: a response to'institutional culture' and (in)-competence in higher education -- Performance = leadership: shifting institutional research performance -- Increasing darkness: combining toxic leadership and volatility, uncertainty, complexity, and ambiguity (vuca) -- The seven deadly narratives of leadership -- Perpetuating inequality in education: valuing purpose over process in educational leadership -- Why leaders are not always to blame: from'free will' to responsible action -- About the authors -- Index.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Leadership -- Moral and ethical aspects; Business ethics; Business & Economics -- Leadership; Management: leadership and motivation